A constrained optimization solution for Caughey damping coefficients in seismic analysis. Issue 3 (2nd May 2017) - Pan, Danguang; Li, Chenfeng
Abstract : Purpose: Extended from the classic Rayleigh damping model in structural dynamics, the Caughey damping model allows the damping ratios to be specified in multiple modes while satisfying the orthogonality conditions. Despite these desirable properties, Caughey damping suffers from a few major drawbacks: depending on the frequency distribution of the significant modes, it can be difficult to choose the reference frequencies that ensure reasonable values for all damping ratios corresponding to the significant modes; it cannot ensure all damping ratios are positive. This paper aims to present a constrained quadratic programming approach to address these issues. Design/methodology/approach: The new method minimizes the error of the structural displacement peak based on the response spectrum theory, while all modal damping ratios are constrained to be greater than zero. Findings: Several comprehensive examples are presented to demonstrate the accuracy and effectiveness of the proposed method, and comparisons with existing approaches are provided whenever possible. Originality/value: The proposed method is highly efficient and allows the damping ratios to be conveniently specified for all significant modes, producing optimal damping coefficients in practical applications.